Public Attention Gap Between Climate Change and Food Security: A Google Trends Study in Indonesia - Gunawibawa, Eka Yuda; Firdaus, Feri; Pratama, Prayoga Ardhi (KOMUNIKA, 2026)
Climate change constitutes a globally significant issue that has garnered extensive attentionwithin digital communication due to its impacts across various sectors of society, includingfood security. This study examines the information-seeking behavior of Indonesian internetusers concerning climate change and food security to acquire insights into the public's recognition of the relationship between these two issues. Employing a quantitative descriptive-correlational methodology, the research employs Google Trends data from May to August 2025, analyzing the relative search volume (RSV) of keywords associated with climatechange, its impacts, mitigation, adaptation, and food security, complemented byAutocorrelation Function (ACF) and Cross-Correlation Function (CCF) analyses. The resultsindicate a very strong correlation between public interest in climate change and searchesrelated to its impacts (r = 0.97), whereas the direct correlation with food security searches iscomparatively weak (r = 0.24); interest in mitigation and adaptation similarly remainsconsistently low. Nonetheless, CCF analysis demonstrates that attention to climate changeand food security becomes more closely aligned after a time delay, with strengtheningobserved at short lags of two to three days (r = 0.41–0.46) and at longer lags of approximatelythree months (r up to 0.74). This suggests that public concern regarding climate change is notconsistently or immediately associated with food security issues but may become connectedover time. The study provides valuable insights into the structure and temporal dynamics ofpublic attention within the digital domain and emphasizes the necessity for communicationstrategies that explicitly and promptly link climate change with food security.